Swoboda wyboru prywatnoprawnej formy działania administracji gospodarczej w polskiej i niemieckiej doktrynie prawa publicznego - Sancewicz, Paweł (Studia Prawa Publicznego, 2019)
The purpose of this paper was to present views of both Polish and German public law doctrine on the issue of the possibility to choose a legal form of implementation of public tasks by the public administration. This issue is not only a theoretical matter because currently administration has to cope with increasingly complex and complicated public tasks that must be implemented. The article first explains the concept of the legal forms of action, distinguished from the measures available in administration. Next, the freedom of choice of the legal form of action as well as the instances of its abuse are analysed. The considerations carried out in the article allow to adopt the position that the choice of the legal form of action by public administration cannot be actually prejudged under Polish law. The main limitation of the freedom to choose the legal form of action is contained in Article 7 read in connection with Article 2 of the Constitution of the Republic of Poland which stipulate a legal framework that ought to embrace them. There is also a concern that the authorities may abuse certain forms of action in order to, for example, avoid certain administrative procedures or to achieve desired fiscal objectives. As indicated in the course of the analysis, the German doctrine and practice encountered similar problems, and now the experience and undoubted successes of German law and practice could be a significant inspiration for Polish lawmakers in this area. De lege ferenda, it is necessary to propose the introduction of legal regulations that will enable or facilitate a free choice of the legal form of action by administrative bodies. However, establishing such regulations will only be possible and and effective when the administrative agreement becomes part of the Polish legal system.